2013
DOI: 10.3109/11038128.2013.868033
|View full text |Cite
|
Sign up to set email alerts
|

The influence of daily routines on engaging in diabetes self-management

Abstract: Objective In contrast to previous research concerning the importance of routines in occupational engagement, most of which have largely focused on the routines of children and families, in this study a qualitative methodology was used to understand how routines function in a specific occupation: diabetes self-management (DSM). Methods Ten low-income women participated in a multiple-methods study that involved completing a time-geographic diary (TGD) and participating in a TGD interview. Results Findings re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 40 publications
(44 reference statements)
0
35
0
Order By: Relevance
“…For instance, Sanders and Van Oss [46] found that remembering to take medications involved behavioral routines associated with meals, personal care, or bedtime. Indeed, the success of new treatment regimens for emergent disease probably requires evaluating and adjusting individuals’ existing behavioral routines [47]. We sought to understand how such routines might promote everyday remembering but also create risks for memory failures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sanders and Van Oss [46] found that remembering to take medications involved behavioral routines associated with meals, personal care, or bedtime. Indeed, the success of new treatment regimens for emergent disease probably requires evaluating and adjusting individuals’ existing behavioral routines [47]. We sought to understand how such routines might promote everyday remembering but also create risks for memory failures.…”
Section: Introductionmentioning
confidence: 99%
“…Methods included having each participant complete the Diabetes Care Profile (Fitzgerald et al . ), participate in a semi‐structured interview, photograph aspects of their daily life they associated with DSM (past and present) and participate in a photo‐elicitation interview (Harper , Fritz & Lysack ), and complete a time‐geographic diary (TGD) with participation in a subsequent TGD interview (Pentland & Harvey , Michelson , Fritz ). Each participant took between 5 and 16 weeks to complete data collection and was compensated one $100.00 (visa gift card) for their time and effort.…”
Section: Methodsmentioning
confidence: 99%
“…Pilot intervention studies were: Piven & Duran, 2014;Haltiwanger & Galindo, 2013;Haltiwanger, 2012a;Haltiwanger, 2012b;Haltiwanger & Brutus, 2012). Exploratory studies were also published (Thompson, 2014;Fritz, 2013;Pyatak et al, 2013a;Pyatak et al, 2013b;Piven & Nazeran, 2013;Pyatak, 2011a;Pyatak, 2011b;Hwang et al, 2009), suggesting the need for intervention.…”
Section: Implications For Practicementioning
confidence: 98%
“…Fritz (2013) stated that life situations affected one's ability to change established habits and daily occupations, and that social influences can be problematic barriers or be supportive.…”
Section: Introduction the Diabetes Epidemicmentioning
confidence: 99%